POLITIK EKOLOGI DALAM MENGATASI PENCEMARAN LINGKUNGAN (STUDI PADA DESA SRIGUNUNG KECAMATAN SUNGAI LILIN KABUPATEN MUSI BANYUASIN) - Afriany, Deany; Akhyar, Taufik; Fahrudin, Aziz (PRAJA: Jurnal Ilmiah Pemerintahan, 2026)
This study is entitled "Ecological Politics in Addressing Environmental Pollution in (A Study in Srigunung Village, Sungai Lilin District, Musi Banyuasin Regency)." The purpose of this study is to analyze the impact of environmental pollution caused by palm oil industry activities on the Srigunung Village community and to examine the dynamics of power relations between the company, the government, and the community from an ecological politics perspective. This study uses a qualitative approach with a case study method, using data collection techniques such as in-depth interviews, field observations, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the industrial activities of PT Srigunung Inti Argo Persada have caused water, air, and soil pollution, which has a direct impact on the health and well-being of the surrounding community. The people of Srigunung Village experience a declinein their quality of life due to industrial waste, yet they have weak bargaining power due to the dominance of corporate power and weak enforcement of environmental law by the local government. From an ecological politics perspective, this condition reflects structural inequality and ecological injustice, where economic gain is prioritized over environmental sustainability and the community's right to a healthy environment. This research emphasizes the importance of implementing environmental policies that support ecological justice, increasing government oversight, and strengthening community participation in sustainable environmental management.